Spillover effects of US QE and QE tapering on African and Middle Eastern stock indices - Stephanos Papadamou; Nikolaos A. Kyriazis; Panayiotis G. Tzeremes (Journal of Risk and Financial Management, 2019)
In this paper, we study spillover effects on the stock markets of six African and nine Middle Eastern emerging economies before, during, and after the implementation of unconventional monetary policies by the United States Federal Reserve (US Fed). Weekly data covering the pre-quantitative easing (pre-QE) period, the three phases of QE, and the QE-tapering period were adopted. The methodologies employed here for detecting dual causality were as follows: classical, dynamic, and time-varying Granger causality tests. The results indicate that the Fed's non-conventional actions weakened the Fed's monetary policies' impact on the stock indices of these emerging countries. Interestingly, there is evidence that two African and three Middle Eastern countries-all different according to each of the specifications used in the methodology-were affected by the tapering of unconventional US monetary practices.
Keywords: E52; E58; G12; 330; unconventional monetary policy; stock indices; Africa; Middle East